Alonto's Views On Conveying The Moderation Of Islamic Message Through Policy Integration Of The Philippine Government - Mohammad Nashief S. Disomimba; Kalsom Ali (Universiti Sains Islam Malaysia, 2024)
This paper examines the contributions of Alonto to the development of moderation of Islamic and western education in the Philippines, and it will clarify his Parliamentary struggle, his establishment of Islamic University of the Philippines and his views on Islamic education. The tendency of giving priority to discuss Alonto’s major contributions to the development of moderation of Islamic and western education in the Philippines is to clarify and trace the hidden and explore the reality of moderation between Islamic and western education and its impact to the communities in the Philippines. To address this limitation, an analytical study is conceived to foreground of his major contributions to the development of Islamic and western education in the Philippines. The objectives of this study is to identify and trace the development of moderation of Islamic and western education, to understand its reality, to summarize the views of Alonto’s Islamic and western education in the Philippines. Discourse Analysis will be used in this study in order to identify the elements of Alonto’s views on moderation of islamic and western education. The study singles out first that the Alonto’s moderation of Islamic and western education is no dichotomy to disconnect its teachings and understanding to each other. His approach to spread and development of moderation of Islamic and western education is primary a combination of his western educational background grounded based on the the Holy Qur᾽ān, and Hadīth. At the end, the study gives framework on Alonto’s views on the development of moderation of Islamic and western education in the Philippines.